Language Learning Strategies Used by Extrovert and Introvert Students in English as a Foreign Language Speaking Classes - Afriyanti Yusuf; Nonny Basalama; Indri Wirahmi Bay (Univeristas Negeri Gorontalo, 2021)
The students in Indonesia are from different cultures, languages, and personality traits (extrovert and introvert). Therefore, recognizing students’ personality traits and their language learning strategy may be effective to help teacher design an effective teaching strategies. The study, therefore, intends to find out the typical language learning strategies used by the extrovert and introvert students in English speaking class. The participants of this study were the fourth semester students in English Department of Gorontalo State University. This research used two models of questionnaire. They were the McCroskey’s introversion scale by Richmond & McCroskey (1998) to determine the personality type for each subject and Strategy Inventory for Language Learning (SILL) by Oxford’s (1990) to see their learning strategy. The findings were explained by using the theory of language learning strategies by O’Malley and Chamot (1990). The result shows that the extrovert students used more language learning strategies highly frequently than introvert students with 12 items compared to introvert students with only 10 items. The most strategies used by extrovert students were cooperating and empathizing with others with 66.7% in always used, while the most strategy used by introvert students was note taking with 66.7% in often used.